Tannin with sodium carbonate: A single additive for poured earth concrete with tropical soils - Lily Walter; Gildas Medjigbodo; Yannick Estevez; Laurent Linguet; Ouahcène Nait-Rabah (Results in Engineering)
Building sustainable earth construction to replace cement concrete is a major challenge in fast-developing tropical regions. Poured earth, shaped like concrete, offers a cost-effective and eco-friendly alternative. Poured earth usually relies on industrial dispersants and hydraulic binders to fluidify and solidify the soil paste. However, these additives strongly increase environmental costs. Recent studies have highlighted the potential of tannins, which are organic extracts from wood, as an eco-friendly alternative. In particular, tannins combined with iron oxides can fluidify soils at an elevated pH, and chemical reactions between tannins and iron oxides lead to rapid solidification, enabling rapid unmolding and improving water resistance. Tropical soils naturally have a high iron oxide content. This study investigated whether tannins could react with the iron oxides naturally present in tropical soil and be used as a single additive for poured earth. Optimal reactions between soils, tannins and iron oxides require an elevated soil pH, and tannins were combined with sodium carbonate (Na2CO3), a low-cost, eco-friendly alkali. Mortars prepared with different dosages of tannin+Na2CO3 were tested and compared to the industrial dispersant sodium hexametaphosphate (NaHMP), using three tropical soils from French Guiana. Results showed that both tannin+Na2CO3 and NaHMP could fluidify the three soils, improved mechanical strength and water resistance, and reduced initial water content and shrinkage. However, tannin+Na2CO3 induced faster solidification, which was attributed to the formation of ferric tannate observed by infrared spectroscopy (ATR-FTIR). This study paves the way for designing poured earth with tropical soil using a single, largely bio-sourced additive: tannin+Na2CO3.